Are poverty and deprivation relevant to general practice in 2021?. Issue 10 (October 2021) - Butler, Daniel
February 2021 marked 50 years since Dr Julian Tudor Hart's landmark paper described the 'Inverse Care Law'. This article explores how applicable the 'Inverse Care Law' is today. How do poverty and deprivation have an impact on general practice today? We learn about the health effects of smoking, obesity and age, but it is important to also understand how relevant deprivation and socioeconomic status are to the health of our patients.